Development of Innovation Capability Model: Analysis of e-CRM and Risk Perceptions of Covid-19 in Bogor City MSMEs - Yanita Ella Nilla Chandra; Husnil Barry (Jurnal Manajemen dan Kewirausahaan, 2022)
The phenomenon of the commercial revolution 4.0 encourages MSME actors to comply with current trends in order that the goods produced may be competitive. Creative enterprise merchandise require innovation competencies with a view to produce advanced merchandise. This study  takes a look at discusses improvement troubles withinside the MSME quarter that are despite the fact that restricted in conventional organization control, inadequate fine of human assets, manufacturing scale and strategies, low innovation functionality and confined get admission to to economic establishments, especially banking. The growth the variety of enterprise actors primarily based totally on facts from the Cooperatives Office the town of Bogor in 2021 with a mean growth of 6.141% of all forms of organizations isn't always matched with the aid of using trends the subject of innovation to assist enhance the advertising overall performance of SMEs the town of Bogor. Where in enhancing the capacity of innovation, it's miles anticipated to synergize with Customer Relationship Marketing or CRM such as numerous information, consumer involvement, long-time period partnerships and technology-primarily based totally trouble fixing in developing enterprise overall performance.